Across-language masculinity of oceans and femininity of guitars: Exploring grammatical gender universalities - Dubenko, Elena (Frontiers in Psychology, 2022)
This is the first cross-language study that reveals the nouns which have invariable masculine or feminine grammatical gender assignments in ten gendered languages from different lnguage groups and families. The research gives evidence that in many cases masculine or feminine universality of the analyzed entities has semantic motivation, i.e., the grammatical gender of the entity correlates with either traditional masculine/feminine connotations, or cultural and symbolic implications. The findings of the study also testify thematic preferences, as the greatest number of masculine grammatical gender universals is found among the nouns that denote artefacts, while femonine grammatical gender universals are predominantely linked to abstract concepts. The circumstance that grammatical gender universals do exist, has a cognitive significance.Since in a psycholinguistic perspective, grammatical gender is viewed as a built-in personification pattern for speakers’ mental representations, the research presents cross-linguistic constants in conceptualizing the basic natural kinds, artefacts and abstract concepts denoted by the considered nouns as ‘male’ or ‘female’.